The Emerging Role of Mast Cells in Response to Fungal Infection - Yu, Miao; Song, Xiao-ting; Liu, Bo; Luan, Ting-ting; Liao, Shuang-lu; Zhao, Zuo-tao (Frontiers in Immunology, 2021)
Mast cells (MCs) have been considered as the core effector cells of allergic diseases. However, there are some evidence suggesting that MCs are involved in the mechanisms of fungal infection. MCs are mostly located in the border between host and environment and thus may have easy contact with the external environmental pathogens. . These cells express receptors which can recognize pathogen-associated molecular patterns such as Toll-like receptors (TLR2/4) and C-type Lectins receptors (Dectin-1/2). Currently, more and more data indicate that MCs can be interacted with some fungi (Candida albicans, Aspergillus fumigatus and Sporothrix schenckii). It is demonstrated that MCs can enhance immunity through triggered degranulation, secretion of cytokines and chemokines, neutrophil recruitment, or provision of extracellular DNA traps in response to stimulation by fungi. In contrast, the involvement of MCs in some immune response may lead to more severe symptoms, such as intestinal barrier function loss, development of allergic bronchial pulmonary aspergillosis and increased area of inflammatory in S. schenckii infection. This suggests that MCs and their relevant signaling pathways are potential treatment regimens to prevent the clinically unwanted consequences. However, it is not yet possible to make definitive statements about the role of MCs during fungal infection and/or pathomechanisms of fungal diseases. In our article, we aim to review the function of MCs in fungal infections from molecular mechanism to signaling pathways, and illustrate the role of MCs in some common host-fungi interactions.